From Hydrology to Hydroarchaeology in the Ancient Mediterranean An Interdisciplinary Approach - Polizzi, Giovanni; Ollivier, Vincent (2024)
From Hydrology to Hydroarchaeology in the Ancient Mediterranean: An interdisciplinary approach is devoted to the study of water management in ancient cities. It compares the approaches and methods adopted by researchers from different disciplinary sectors to identify the water conditions of past societies and to highlight the measures they have taken to adapt to their water resources. Deriving from an interdisciplinary meeting held in Aix-en-Provence (Mediterranean House of Human Sciences) in 2019, it brings together seven articles that present the innovative results of collaborations between archaeologists and environmental scientists, geologists, geomorphologists, and climatologists in particular. After an introduction that situates the discussions conducted in Aix-en-Provence within the framework of the Watertraces project, funded by the A*Midex foundation (Aix-Marseille University), most of the articles focus on the Sicilian situation. An initial synthesis covers all aspects of the question, followed by four case studies ranging from the 4th century BC to the 1st century AD. Case studies on Agrigento, Termini Imerese/Thermai Himerenses, Alesa/Halaesa, Solunte and Tyndaris are presented. The focus then moves to southern Italy (the Terme di Baia), and to Aegean Greece (the sanctuary at Delphi).